Demographic Challenges – Labour Law Responses - Jakab, Nóra (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
Demographic challenges raise complex cross-policy issues. This chapter addresses the narrow issues of labour law regulation and the broader issues of employment and social security in the context of the ageing society as a demographic challenge. The chapter first examines issues related to labour law issues, which is the broad framework within which we can present the qualitative criteria for a life worthy of the active and inactive (i.e. once working) person. To find solutions to the demographic challenges, the chapter briefly summarises the results of two recent studies. A well-functioning social system goes hand in hand with a well-functioning economy. The challenge is combining both economic and social aspects in a balanced manner.Keywords: labour law regulation, employment, social security, sustainability, human resources, generation gaps